Empowerment of posyandu cadres as a strategy for overcoming stunting in children in Borneang Village - Cintu Waisawati; Nirmalasari Nirmalasari; Salmawati I Ishak; Fransisca Noya; Khuzaifah Khuzaifah; Lisda Widianti Longgupa; Christina Entoh; Nurfatimah Nurfatimah; Kadar Ramadhan; Sony Bernike Magdalena Sitorus; Putri Mulia Sakti; Febti Kuswanti; Marlina Fitriya Lailatul K (Universitas Muhammadiyah Magelang, 2024)
Stunting is a growth and development disorder in children caused by a lack of nutritional intake in the first 1000 days of life (HPK). It is a national issue requiring special attention from the government because stunting can hinder human resource potential and is linked to the health level of an area. Therefore, preventing stunting becomes a shared responsibility, with Posyandu cadres, as community representatives, playing an important role in implementing effective interventions to reduce stunting rates. This activity aims to broaden the insight of Posyandu cadres. Through this effort, it is hoped that Posyandu services will improve, leading to a reduction in stunting rates. The activity utilized the lecture and question-and-answer method. As a result, the average knowledge of Posyandu cadres increased from 42% to 100%.